Direction‐Sensitive Magnetophotonic Surface Crystals. Issue 10 (6th October 2021) - Rowan-Robinson, Richard M.; Hurst, Jérome; Ciuciulkaite, Agne; Chioar, Ioan-Augustin; Pohlit, Merlin; Zapata-Herrera, Mario; Vavassori, Paolo; Dmitriev, Alexandre; Oppeneer, Peter M.; Kapaklis, Vassilios
Abstract : Magnetophotonic Crystals In article number 2100119 by Richard M. Rowan‐Robinson, Alexandre Dmitriev, Vassilios Kapaklis, and co‐workers, microscale magnetophotonic surface crystals are revealed by building arrays of magnetoplasmonic nanoantennas with nanosized rare‐earth transition metal ferrimagnetic TbCo alloys, displaying perpendicular magnetic anisotropy. Magneto‐optics is dramatically enhanced in such crystals via nanoantennas plasmons and their coupling into collective surface lattice modes. The result is a highly light‐direction‐sensitive optical surface with nanomagnetic functionality for the plasmon‐assisted all‐optical magnetization switching.